The Effect of Snakehead Fish (Channa striata) Extract on Inflammation Reaction of Skin Wound Tissue in Rattus novergicus Wistar Strain - Nanda Amalia Ramadhanti; Willy Sandhika; Agung Dwi Wahyu Widodo (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Snakehead fish has been associated with wound healing due to its high albumin content. Albumin can accelerate the inflammatory process so that tissue repair will be faster. Lack of albumin protein causes a person tend to experience prolonged wound healing. Purpose: This study aims to prove the effect of snakehead fish extract on the number of macrophages and blood vessels on the inflammatory reaction of skin wound tissue in rats. Methods: Laboratory experimental design with a total sample size of 27 male rats have undergone incisions, divided into 3 random groups: control group was given aquadest, treatment group 1was given aquadest and 50% extract of snakehead fish, and treatment group 2 was given 100% extract of snakehead fish. The rat’s skin wound tissues were taken on day 5 and observed under the microscope. The average number of macrophages and blood vessels on granulation tissue that formed at the base of the wound were counted and then performed data analysis. Result: In this study, we found a down wards trend in the average number of macrophages and blood vessels in treatment group 1 and treatment group 2. The control group and the treatment group 2 showed a significant difference, however, between the other groups did not show significant difference. Conclusion: There is a significant effect of giving 100% snakehead fish extract on decreased macrophages and blood vessels in the inflammatory reaction of skin wound tissue.